2005
DOI: 10.1029/2004jd005359
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the global impact of aerosols on tropospheric oxidants

Abstract: [1] We present here a fully coupled global aerosol and chemistry model for the troposphere. The model is used to assess the interactions between aerosols and chemical oxidants in the troposphere, including (1) the conversion from gas-phase oxidants into the condensed phase during the formation of aerosols, (2) the heterogeneous reactions occurring on the surface of aerosols, and (3) the effect of aerosols on ultraviolet radiation and photolysis rates. The present study uses the global three-dimensional chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
253
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(266 citation statements)
references
References 82 publications
(128 reference statements)
6
253
1
Order By: Relevance
“…They found no significant change in the global O 3 burden, but significant regional variations in surface O 3 concentrations due to heterogeneous reactions and to the aerosol photochemical effect (e.g., O 3 decrease by 10 -15% over northeastern China and Yellow Sea and by 10-40% over India). Tie et al [2005] found a decrease in surface O 3 concentration ranging from 5 to 15% because of heterogeneous reactions of N 2 O 5 , HO 2 , O 3 , CH 2 O and HNO 3 on sulfate, soot and dust particles in polluted regions and ranging from 10 to 30% in dust source regions. The effect of heterogeneous reactions on dust on O 3 concentration remains largely uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They found no significant change in the global O 3 burden, but significant regional variations in surface O 3 concentrations due to heterogeneous reactions and to the aerosol photochemical effect (e.g., O 3 decrease by 10 -15% over northeastern China and Yellow Sea and by 10-40% over India). Tie et al [2005] found a decrease in surface O 3 concentration ranging from 5 to 15% because of heterogeneous reactions of N 2 O 5 , HO 2 , O 3 , CH 2 O and HNO 3 on sulfate, soot and dust particles in polluted regions and ranging from 10 to 30% in dust source regions. The effect of heterogeneous reactions on dust on O 3 concentration remains largely uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers also assessed the effect of aerosols on trace gases through the modification of photolysis rates. In general this effect on surface O 3 concentrations is found to be globally small [Bian and Zender, 2003;Tie et al, 2005], but can be significant in aerosol source regions such as eastern Asia, Europe, United States and Sahara [Tang et al, 2003;Martin et al, 2003]. Note that the comparison between these studies remains somewhat difficult as the representation of aerosols (e.g., bulk approach For relative humidity (RH) !…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerosol Surface Area (SA) was calculated from the observed aerosol mass concentrations. We assumed that aerosols were spherical, and the mean radius and mass density of sulfate and soot were taken from Tie et al (2005) (sulfate: 0.24 µm, 1.7 g cm −3 ; soot: 0.04 µm, 1.0 g cm −3 ), with a lognormal distribution. Dust and sea salts were divided into 4 bins (0−1 m; 1−2.5 m, 2.5−5 m, 5−10 m), with mass density of 2.2 g cm −3 and 2.65 g cm −3 , respectively.…”
Section: Box Modeling Calculations a Box Model Descriptionmentioning
confidence: 99%